MENINGKATKAN EFEKTIVITAS DAKWAH BKMT MELALUI MEDIA SOSIAL INSTAGRAM - Ichsana, Lily Kamalia; Nurhasanah, Nurhasanah; Suaebah, Siti; Ayu Kartika, Khofifah (Moderation | Journal of Islamic Studies Review, 2024)
Social media has become an essential part of modern life, with instagram being one of the most widely used platforms. With over a billion active users, Instagram offers great potential as a tool for a variety of purposes, including da'wah. Da'wah is the process of conveying Islamic teachings to the community, which requires an effective approach to reach a wider and diverse audience. The Contact Body of the Taklim Council (BKMT), as an organization consisting of teenagers and mothers from various taklim councils throughout Indonesia, faces challenges in using Instagram for da'wah purposes. These challenges include a lack of understanding of technology among BKMT members, limited resources, and the need to produce content that is interesting and relevant to young people.